Elite sports training as model for future internet practices? - Eriksson, M. (2013)
This paper presents Vndings from an in situ study made at CAR (Centre d`Alt Rendiment) - a high performance center for athletes in St Cougar outside Barcelona, Spain. The study was conducted as part of the FP7 funded Experimedia project1 exploring the application of future media technologies within a sports context together with CAR. The main focus of Experimedias activities at CAR is the development of technology that directly impacts the sports training such as the use of high-deVnition video documentation and vizualisation of sensor data. As part of Experimedia, the study of which this paper is concerned was conducted in order to give insight into the practices of the everyday life of athletes, coaches and staU at CAR. The study itself consisted of observations as well as interviews with athletes, coaches and staU and the study of printed and digital material produced by CAR. Instead of presenting the Vnding from this in a sports performance context, this paper will reWect on the suitability of studying elite athletes and their life at the training center as a way of gaining knowledge about possible applications and use of future media technologies. The paper will give a background to the life at CAR then give examples of how the study provided opportunities of learning in the context of future internet use. Finally there is a discussion of the suitability of studying future internet practices with Veld studies in sites such as CAR as well as possible directions for future research.